Seasonality of livebirths and climatic factors in Italian regions (1863-1933) - Gabriele Ruiu; Marco Breschi (Historical Life Course Studies)
Birth seasonality is a phenomenon that characterizes almost all the populations of the world. In spite of this, the causes underlying these seasonal fluctuations represent an as yet unsolved puzzle. Two main theoretical approaches have been proposed to explain birth seasonality. The first encompasses a social explanation and emphasizes the role of social, economic and cultural factors in determining the optimal moment (from a social perspective) for conception (e.g., according to the cycle of agricultural workload, religious festivity, marriage seasonality, etc.). The second theoretical approach encompasses an environmental explanation and focuses on the role that climatic factors (e.g., temperature, rainfall, light intensity, etc.) play in determining the optimal moment of conception from a biological perspective. Our paper may be collocated in the latter strand of the literature. The aim is to investigate the effects of temperature on conceptions, and subsequently on the seasonality of livebirths, while controlling for a possible social confounding effect, i.e. the seasonal pattern of marriage. To achieve this end, we empirically investigate the role of temperature as well as that of marriage seasonality in Italian regions for the period stretching from the Italian unification to the eve of World War II. We find that extreme temperatures (both cold and hot) negatively affect the number of births. At the same time, marriage seasonality also seems to be an important explicative factor of the seasonal fluctuation of live births.